Collection from Riyad-us-Saliheen: With Commentary on Ahadith - Imam An- Nawawi; Ahadith selected and collected by Safiur-Rahman Mubarakpuri ; Translated by Muhammad Amin Abu Usamah Al-Arabi Bin Razduq (Lahore Darussalam, 2011)
This new full color edition of Riyad-us-Saliheen is a collection of the most important hadith from the 2 volume full edition. It has Arabic text followed by English translation and commentary below those. Imam Nawawi was a great scholar of Hadith and Fiqh of his time. He compiled Riyad-us-Saliheen which acclaimed an important position in the Hadith Collections. It is an extremely popular and useful compilation of authentic hadith. Commentaries on the Ahadith were added by Hafiz Salahuddin Yusuf of Pakistan. Keeping in view the problems of our times, we wished to print a concise volume of Riyad-us-Saliheen. For this volume, Sheikh Safi-ur-Rahman Mubarakpuri has made the selection of Ahddith.
Keywords: Hadith -- Texts -- Early works to 1800.